Terri Schiavo and Five Wishes - Kay Rosenthal (Rural Nurse Organization; Binghamton University, 2012)
My call to RNO members as Executive Director of RNO is to get active in your community. My challenge to all of you is to educate your community members about health and health care issues. Here's a great way to take a national event and bring it to the local level. Terri Schiavo was in the news when a federal judge refused to order the reinsertion of her feeding tube March 22, 2005. The parents of this woman with brain-damage filed a notice of appeal. To me, this is what Five Wishes is all about. What did Terri want when she was able to speak for herself? What do you want when you can no longer speak for yourself and who will speak for you?